Physical Conflict During Pregnancy: A Socioecological, Cross-Cultural Examination of Risk and Protective Factors for New Zealand Women. (September 2021) - Bird, Amy L.; Underwood, Lisa; Berry, Sarah; Grant, Cameron C.; Gulliver, Pauline; Fanslow, Janet; Atatoa Carr, Polly E.; Fa'alili-Fidow, Jacinta; Morton, Susan M. B.
Participants were 5, 831 women in their third trimester of pregnancy, part of a large, longitudinal, pre-birth national cohort study. Women reported on their experience of pushing and shoving, throwing or breaking objects within their relationship over the past month. Univariable regression models examined the association of a large number of potential risk and protective factors. Those significant at the univariable level were carried forward into final multivariable analyses, stratified by New Zealand's four main ethnic groups: European, Māori, Pacific, and Asian peoples. Relationship commitment, reduced family cohesion, and perceived stress were associated with increased risk across ethnic groups.